Sistem Bas UTHM Menggunakan Android dan kod QR - Samsulbahri, Muhammad Amirul Ikhmal; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2021)
This system is an Android based system that can record the number of students boarding and disembarking the bus and there are three problem statements discussed in this project which is bus drivers find it difficult to count and limit the number of students boarding the bus at one time, the Student Affairs (HEP) find it difficult to determine the number of buses needed at one time and students are unable to get off at the desired stop due to congestion in the buses. The objective of this project is to design a system using the Android programming approach, develop a system using QR codes and the Android platform and perform alpha testing on the system to target users. The software development methodology used to develop this system is the Waterfall Model. The implementation and testing results show that this application is developed according to the stated objectives. Overall, this system was successfully completed in accordance with the stated objectives, and it is hoped that a more detailed study is done so that the system can be developed into a system that is beneficial to all UTHM residents.